2018
DOI: 10.1158/2159-8290.cd-17-0787
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predictors of Response to Systemic Therapy in Esophagogastric Cancer

Abstract: The incidence of esophagogastric cancer is rapidly rising, but only a minority of patients derive durable benefi t from current therapies. Chemotherapy as well as anti-HER2 and PD-1 antibodies are standard treatments. To identify predictive biomarkers of drug sensitivity and mechanisms of resistance, we implemented prospective tumor sequencing of patients with metastatic esophagogastric cancer. There was no association between homologous recombination defi ciency defects and response to platinum-based chemothe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
303
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(325 citation statements)
references
References 34 publications
19
303
3
Order By: Relevance
“…Further, pathologic review of surgical specimens treated with chemotherapy demonstrated that no patient with an MSI‐H tumor had evidence of treatment response. Similarly, in a study from MSKCC including nine MSI‐H patients, PFS was shorter in MSI‐H patients who received standard first‐line cytotoxic chemotherapy compared to non‐MSI‐H patients, median PFS 4.8 versus 6.9 months, HR 0.4; P = 0.027 (log‐rank test) . Moreover, of 40 patients with metastatic gastric and esophageal cancer treated with checkpoint blockade immunotherapy at MSKCC, 5 patients experienced durable responses and were alive 19.5‐44.7 months following initiation of immunotherapy after failure of standard cytotoxic chemotherapy regimens.…”
Section: Msi‐h Esophagogastric Adenocarcinoma and Checkpoint Blockadementioning
confidence: 94%
See 1 more Smart Citation
“…Further, pathologic review of surgical specimens treated with chemotherapy demonstrated that no patient with an MSI‐H tumor had evidence of treatment response. Similarly, in a study from MSKCC including nine MSI‐H patients, PFS was shorter in MSI‐H patients who received standard first‐line cytotoxic chemotherapy compared to non‐MSI‐H patients, median PFS 4.8 versus 6.9 months, HR 0.4; P = 0.027 (log‐rank test) . Moreover, of 40 patients with metastatic gastric and esophageal cancer treated with checkpoint blockade immunotherapy at MSKCC, 5 patients experienced durable responses and were alive 19.5‐44.7 months following initiation of immunotherapy after failure of standard cytotoxic chemotherapy regimens.…”
Section: Msi‐h Esophagogastric Adenocarcinoma and Checkpoint Blockadementioning
confidence: 94%
“…Although the TCGA analysis determined that 22% of gastric cancers are MSI‐H, which are predicted to respond to checkpoint blockade immunotherapy due to high mutational burdens and predicted high neoantigen expression, an analysis of 295 metastatic gastric and GEJ cancers from Memorial Sloan Kettering Cancer Center (MSKCC) found that only 9 (3%) tumors were MSI‐H . There are several differences between the TCGA and MSKCC cohorts that may explain the difference in MSI‐H tumor prevalence.…”
Section: Msi‐h Esophagogastric Adenocarcinoma and Checkpoint Blockadementioning
confidence: 99%
“…For somatic gene mutations, the development of targeted cancer‐gene panels for genomic profiling will also be indispensable for precision oncology. For instance, the Memorial Sloan Kettering‐Integrated Mutation Profiling of Actionable Cancer Targets (MSK‐IMPACT) gene panel used by Janjigian et al represents one powerful tool that can be applied to prospective genomic profiling of patients for therapeutic decision‐making. Such cancer gene panels represent a cost‐effective and clinically feasible method that will enable the stratification of patients based on actionable gene alterations associated with FDA‐approved targeted therapies, as demonstrated by both Ichikawa et al and Kuboki et al …”
Section: From Bench To Bedside: Translational and Clinical Utility Ofmentioning
confidence: 99%
“…Furthermore, it is important to note that patient cohorts defined by a common biomarker, such as ERBB2 amplification and/or overexpression, may still show distinct underlying tumor biologies. For instance, Janjigian et al noted substantial heterogeneity in co‐occurring RAS / PI3K mutations within an ERBB2‐ positive cohort. In particular, ERBB2 ‐positive patients harboring co‐occurring alterations consistent with RAS/PI3K pathway activation were found to benefit less from trastuzumab treatment.…”
Section: Confounding Layers Of Complexities Underlie Gc Classificationmentioning
confidence: 99%
“…The molecular complexity of gastroesophageal adenocarcinoma (GEA) is increasingly understood as a determinant of response to both cytotoxic therapies and, more importantly, receptor tyrosine kinase (RTK)‐directed therapies . Several series have now clearly demonstrated intertumoral and intratumoral heterogeneity of the actionable RTKs human epidermal growth receptor 2 (HER2), epidermal growth factor receptor (EGFR), and MET.…”
Section: Introductionmentioning
confidence: 99%